Effective Proactive and Reactive Defense Strategies against Malicious Attacks in a Virtualized Honeynet - Frank Yeong-Sung Lin; Yu-Shun Wang; Ming-Yang Huang (Journal of Applied Mathematics)
Virtualization plays an important role in the recent trend of cloud computing. It allows the administrator to manage and allocate hardware resources flexibly. However, it also causes some security issues. This is a critical problem for service providers, who simultaneously strive to defend against malicious attackers while providing legitimate users with high quality service. In this paper, the attack-defense scenario is formulated as a mathematical model where the defender applies both proactive and reactive defense mechanisms against attackers with different attack strategies. In order to simulate real-world conditions, the attackers are assumed to have incomplete information and imperfect knowledge of the target network. This raises the difficulty of solving the model greatly, by turning the problem nondeterministic. After examining the experiment results, effective proactive and reactive defense strategies are proposed. This paper finds that a proactive defense strategy is suitable for dealing with aggressive attackers under “winner takes all” circumstances, while a reactive defense strategy works better in defending against less aggressive attackers under “fight to win or die” circumstances.